REVIEW: Symbiosis between the Giant Clams (Bivalvia: Cardiidae) and Zooxanthellae (Dinophyceae) - UDHI EKO HERNAWAN (Biodiversitas Journal of Biological Diversity, 2008)
Giant clams are the largest bivalves in the world that maintain a mutual relationship with zooxanthellae. Individual giant clam can harbor heterogeneous zooxanthellae, at least four taxa in genus Symbiodinium. The Symbiodinium lives in the zooxanthellal tubular system, a tube structure arising from one of the diverticular duct of the clamâ€™s stomach. Since the numbers of zooxanthellae is the one of some significant factors contributing to the clams growth and survival, the giant clams need to adjust the number of zooxanthellae for physiological reason with unclear mechanism. The important role of the symbiotic relationship to the clams can be seen on the survival, growth and nutrition of the clams. There are at least two significant factors determining the symbiosis, i.e. water temperature in related with level of light intensities and ammonium-phosphate rate. Some topic is still unclear, i.e. the determination of species in genus Symbiodinium, the mechanism for adjusting the population numbers of the algae and what kind of environmental factors determining the symbiosis. Thereby further research is still needed to clarify those missing.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: giant clams, zooxanthellae, Symbiodinium, symbiosis